Phytochemical Analysis, Antioxidant and Bone Anabolic Effects of Blainvillea acmella (L.) Philipson - Abdul Rahim, Rohanizah; Jayusman, Putri Ayu; Lim, Vuanghao; Ahmad, Nor Hazwani; Abdul Hamid, Zuratul Ain; Mohamed, Sharlina; Muhammad, Norliza; Ahmad, Fairus; Mokhtar, Norfilza; Mohamed, Norazlina; Shuid, Ahmad Nazrun; Naina Mohamed, Isa (Frontiers in Pharmacology, 2022)
Blainvillea acmella (L.) Philipson [Asteraceae] (B. acmella) is an important medicinal plant native to Brazil, and it is widely known as a toothache plant. A plethora of studies have demonstrated the antioxidant activities of B. acmella and few studies on the stimulatory effects on alkaline phosphatase (ALP) secretion from bone cells; however, there is no study on its antioxidant and anabolic activity on bone cells. The study aimed to evaluate the phytochemical contents of aqueous and ethanol extracts of B. acmella using gas chromatography mass spectrometry (GCMS) along with the total phenolic (TPC) and flavonoid (TFC) contents using Folin-Ciocalteu and aluminum colorimetric methods. The extracts of B. acmella leaves were used to scavenge synthetic-free radicals such as 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2’-azino-bis, 3-ethylbenzothiazoline-6-sulfonate (ABTS), and ferric reducing antioxidant power (FRAP) assays. The bone anabolic effects of B. acmella extracts on MC3T3-E1 cells were measured with 3-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazoium bromide (MTT) at 1, 3, 5, and 7 days, Sirius-red and ALP at 7 and 14 days, and Alizarin Red S at 14 and 21 days. Comparatively, ethanol extract of B. acmella (BaE) contributed higher antioxidant activities (IC50 of 476.71 µg/mL and 56.01 ± 6.46 mg L-ascorbic acid/g against DPPH and FRAP, respectively). Anabolic activities in bone proliferation, differentiation, and mineralization were also higher in B. acmella of ethanol (BaE) than aqueous (BaA) extracts. Positive correlations were observed between phenolic content (TPC and TFC) to antioxidant (ABTS and FRAP) and anabolic activities. Conversely, negative correlations were present between phenolic content and anabolic activity to antioxidant (DPPH) activity. These potential antioxidant and bone anabolic activities in BaE might be due to the phytochemicals confirmed through GCMS and LCTOFMS, revealed that terpenoids of α-cubebene, cryophyllene, cryophyllene oxide, phytol and flavonoids of pinostrobin and apigenin were the compounds contributing to both antioxidant and anabolic effects in BaE. Thus, B. acmella may be a valuable antioxidant and anti-osteoporosis agent. Further study is needed to isolate, characterize and elucidate the underlying mechanisms responsible for the antioxidant and bone anabolic effects